A splice hepadnavirus RNA that is essential for virus replication. - Obert, S (1996)
According to the current model of hepadnavirus gene expression, the viral envelope proteins are produced from unspliced subgenomic RNAs, in contrast to the retroviral mechanism, where the subgenomic env RNA is generated by RNA splicing. We now describe and characterize a novel duck hepatitis B virus RNA species which is derived from the RNA pregenome by loss of a 1.15 kb intron. This RNA (termed spliced L RNA) codes for the large surface protein (L protein), as does the previously described unspliced mRNA (the preS RNA); however, it differs in 5' leader sequence and promoter control. Mutational analysis indicates that the spliced L RNA is functionally important for virus replication in infected hepatocytes and ducks, but not for virus formation from transfected DNA genomes. This suggests that the newly discovered second pathway for L protein synthesis plays a distinct role in an early step in the viral life cycle.